Digital light processing fabrication of mullite component derived from preceramic precusor using photosensitive hydroxysiloxane as the matrix and alumina nanoparticles as the filler. Issue 11 (September 2021) - He, Chong; Liu, Xinger; Ma, Cong; Li, Xilu; Hou, Feng; Yan, Liwen; Guo, Anran; Liu, Jiachen
Highlights: Complex-shaped mullite components were DLP printed based on a hydroxysiloxane/Al2 O3 preceramic precursor strategy. The introduction of hydroxysiloxane can improve the homogeneity and rheological properties of mullite slurry. The introduction of hydroxysiloxane can reduce the sintering temperature of 3D-mullite precursor. A sintering aid AlF3 was employed to promote the sintering reaction between the hydroxysiloxane and the Al2 O3 filler. Abstract: By taking advantage of the low sintering temperatures of the preceramic polymers, stereolithography printed mullite components derived from preceramic polymer precursor containing alumina particles can be sintered at low temperatures. However, due to their high specific surface, nano alumina particles are difficult to be dispersed into the photocurable polysiloxane. Herein, to prepare mullite slurry, a photosensitive hydroxysiloxane was employed as the preceramic polymer matrix while γ-Al2 O3 nanoparticle was added as the active filler. The introduction of photocurable hydroxysiloxane not only improved the homogeneity and rheological properties of mullite slurry but also shorted the ionic diffusion distance of Si-ion and Al-ion during the sintering process. Therefore, 3D mullite preceramic precursor stereolithography printed from hydroxysiloxane-Al2 O3 slurry was endowed with a low sintering temperature around 1400 °C. During the sintering process of preceramic precursor, sintering aid AlF3 can participate in the reaction and further promote the formulation of mullite grains.